Teachers' Strategies in Fostering Students' Intrinsic Motivation in Social Studies Learning In Elementary School - Rivai, Immawati; Mana, Rivai (Golden Ratio of Social Science and Education, 2024)
This study aims to (1) explore teachers' strategies in fostering students' intrinsic motivation in Social Studies (IPS) learning in elementary schools in Makassar City, and (2) identify the obstacles faced by teachers in increasing students' intrinsic motivation. The approach used in this study was qualitative, with a descriptive research design. Data were obtained through classroom observations, interviews with teachers and students, and learning documentation. The results showed that the strategies applied by teachers to foster students' intrinsic motivation included contextual learning, problem-based learning (PBL), providing positive feedback, and using technology. However, the teachers faced several obstacles, including limited time, inadequate facilities, and insufficient professional training. This study suggests improving access to technology, providing further training for teachers, and allocating sufficient time to the curriculum to support the implementation of strategies that can increase students' intrinsic motivation.